Evaluation of selected Philippine germplasm for resistance to rice stem borer (Scirpophaga spp.) using seven morphological traits - Viz, Jerick A.; Pacada, Imeldalyn G. (2024)
Plant morphological structures are one of the primary factors that deter insect pest infestations. In this study, stem borer (Scirpophaga spp.) resistance-related morphological traits of six selected Philippine germplasm were quantified, compared to the resistance check TKM6, and analyzed in three seasons 2018 WS (wet season) 2019 DS (dry season), and 2019 WS using analysis of variance with Tukey’s test (p > 0.05) and hierarchical cluster analysis based on Ward’s method algorithm. These analyses were conducted to support the selection in pre-breeding activities using seven identified morphological traits such as leaf color, flag leaf length, flag leaf width, leaf width, stem diameter, culm length, and length of the 4th internode. Inarciaga resulted with the highest number of statistically comparable structures to TKM6, with six traits, during 2018 WS. Inarciaga, Mukol, and C-4 Dinorado demonstrated two statistically comparable traits to TKM6 during 2019 DS. In 2019 WS, Mukol, and the susceptible TN1 both showed six traits, the highest among the selected germplasm, statistically comparable to TKM6. Thus, cumulative morphological traits similarity to TKM6 revealed that Inarciaga, Mukol, and C-4 Dinorado were good candidate genotypes for morphological phenotype selection. Based on hierarchical cluster analysis, three clusters were reported: Cluster I (Dinorado and C-4 Dinorado), Cluster II (TKM6, Hinumay, and Mukol), and Cluster III (Inarciaga, Red 18, and TN1). Inarciaga and Red 18 were delineated among other germplasm based on the highest number of desirable morphological traits against stemborer such as lesser leaf surface area, narrower stem diameter, and shorter height.
Keywords: Rice disease and pest resistance; Stem borers; Plant germplasm